The effect of graphene on the properties of 8YSZ ceramics rapidly sintered by high-frequency induction heating - Jeong, Seong-Yong; Moon, Byung-Moon; Yoon, Jin-Kook; Hong, Kyung-Tae; Shon, In-Jin (KOREAN ASSOC CRYSTAL GROWTH, INC, 2015)
Despite of many attractive properties, the low fracture toughness of 8YSZ ceramic limits its wide application. One of the most obvious tactics to improve the mechanical properties has been to add a reinforcing agent to formulate a nanostructured composite materials. In this respect, graphene was evaluated as the reinforcing agent of 8YSZ ceramics using high-frequency induction heated sintering (HFIHS). Highly dense alumina-graphene composites with a relative density were obtained within 2 min by HFIHS under a pressure of 80 MPa. The rapid consolidation method allowed the retainment of the nano-scale microstructure by inhibiting the grain growth. The grain size of 8YSZ was reduced significantly by the addition of graphene. The addition of graphene to 8YSZ improved the fracture toughness of 8YSZ-graphene composite.
Keywords: MECHANICAL-PROPERTIES; NANOSTRUCTURED ZRO2; COMPOSITE; ZIRCONIA; GROWTH